Two Cases of Hemophagocytic Lymphohistiocytosis Associated with Disseminated Histoplasmosis Presented with Transient Pancytopenia - Apriany, Novi; Sukorini, Usi; Ratnaningsih, Tri; Asdie, Rizka Humardewayanti; Subronto, Yanri Wijayanti; Hutajulu, Susanna Hilda; Purwanto, Ibnu; Hardianti, Mardiah Suci (Hindawi Limited, 2022)
Transient pancytopenia due to reactive bone marrow suppression often occurs in hemophagocytic lymphohistiocytosis (HLH), a syndrome resulting from excessive immune activation following a severe infection. We reported two cases with pancytopenia and disseminated histoplasmosis accompanied by HLH, initially suspected to be blood malignancies. Our first case documented the relevance between the improvement of pancytopenia and the clearance of Histoplasma capsulatum in serial bone marrow aspirations. The second case showed immense Histoplasma engulfment by the macrophage in relation to a severe clinical condition, followed by improvement of clinical symptoms in accordance with the recovery of pancytopenia. These two cases highlighted the importance of comprehensive and critical analysis for cases with concurrent pancytopenia and severe infection, since it may be that the pancytopenia underlies the severe infection or vice versa.